2004
DOI: 10.1002/jemt.20033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of nerve fibers and their distribution in histologic sections of the human brain

Abstract: The field of quantitative analysis and subsequent mapping of the cerebral cortex has developed rapidly. New powerful tools have been applied to investigate large regions of complex folded gyrencephalic cortices in order to detect structural transition regions that might partition different cortical fields of disjunct neuronal functions. We have developed a new mapping approach based on axoarchitectonics, a method of cortical visualization that previously has been used only indirectly with regard to myeloarchit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Algorithm-based mapping procedures are not limited to the analysis of cytoarchitectonic images, but can be applied to all architectural modalities which reveal a quantifiable, laminar cortical pattern. Typical examples are specimens stained for acetylcholinesterase (AChE; Hackett et al 2001), receptorarchitecture (Geyer et al 1996;Morosan et al 2004b) and myeloarchitecture (Annese et al 2004;Schmitt et al 2004). Recently, Fatterpekar et al (2002) depicted the laminar pattern in some neocortical areas using MR-microscopy in post mortem, fixed human brains.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Algorithm-based mapping procedures are not limited to the analysis of cytoarchitectonic images, but can be applied to all architectural modalities which reveal a quantifiable, laminar cortical pattern. Typical examples are specimens stained for acetylcholinesterase (AChE; Hackett et al 2001), receptorarchitecture (Geyer et al 1996;Morosan et al 2004b) and myeloarchitecture (Annese et al 2004;Schmitt et al 2004). Recently, Fatterpekar et al (2002) depicted the laminar pattern in some neocortical areas using MR-microscopy in post mortem, fixed human brains.…”
Section: Discussionmentioning
confidence: 97%
“…In a myeloarchitectural study, the traditional optical density measurement (e.g. Hopf 1968a) has been extended to structural parameters such as fibre density and orientation (Schmitt et al 2004). …”
Section: Parameter Selectionmentioning
confidence: 99%
“…Since the identical parameters are derived from structure tensor analysis of histological sections, direct comparisons between the two modalities were straightforward. ST analysis is a widely used technique in the realm of digital image and video processing (Bigun et al, 2004) and has previously been applied to human tissue sections (Schmitt and Birkholz, 2010;Schmitt et al, 2004). The application of ST analysis using a local neighborhood (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators have observed distinct rostral-occipital differences, which were designated as FB , FC (B) and FC region (von Economo and Koskinas 1925); 6a, 6, 6p and 6op regions (Sarkissov et al 1955); 39bL, 38b, 39bb, 39c, 40b, 40L, 42d-L and 44a regions (Ngowyang 1934); 6aa, 6ab, 6ba and 6bb regions (Vogt and Vogt 1919;Foerster 1931); the frontomotoric zone of Sanides consists of five sub-regions: 37-42 (Sanides 1962) ( Table 1). Descriptive myeloarchitectonic investigations differentiated up to eight areas (Vogt 1910: area 38-44, 55) (Strasburger 1937: 37-39, 41a, 42, 44, and 55b) and a quantitative mapping study (Schmitt et al 2004a) provided evidence of a subdivision of BA 6 into rostrooccipital parts. At the very least, pigmentarchitectonic findings present a convincing argument for the existence of a homogeneous region (Braak 1980).…”
Section: Introductionmentioning
confidence: 99%